Optimizing greenhouse microclimate for plant pathology: challenges and cooling solutions for pathogen control in arid regions - Yusuf, Abdulmujib G.; Al-Yahya, Fahad A.; Saleh, Amgad A.; Abdel-Ghany, Ahmed M. (Frontiers in Plant Science, 2025)
Crop production using greenhouse technology has become increasingly essential for intensifying agricultural output, particularly in regions with challenging climatic conditions. More so, greenhouses do not only support continuous crop supply but also provide a controlled environment crucial for studying plant-pathogen interaction. Likewise, pests and diseases are a constant threat to crop production, which requires innovative control methods. Providing a suitable and sustainable control method requires a detailed probe into the relationship between plants and biotic disturbance under controlled settings. Therefore this review explores the relationships between plants and pathogens, highlighting the impact of extreme greenhouse microclimates on plant pathology assays. Given the extreme weather conditions in the Arabian peninsula, the efficiency of greenhouses, especially during summer, is compromised without adequate cooling systems. This review discusses the current strategies employed to optimize greenhouse conditions in hot arid regions, aiming to enhance plant health by mitigating pathogen activity while minimizing energy, and water consumption. The review also provides an overview of how microclimatic parameters within greenhouses influence plant-pathogen dynamics, ensuring conditions that are conducive to managing both biotic and abiotic diseases. Additionally, the review aims to evaluate various cooling techniques available and most widely accepted in hot arid regions. Moreover, the performance indicators, principles, and effectiveness of each technique are discussed. Promising advances in the manipulations and combination of these techniques have proven to maintain an appropriate greenhouse microclimate with minimal resource use.